Natural fiber suspensions in thermoplastic polymers. I. analysis of fiber damage during processing - Terenzi, Andrea (2007)
The final properties of the composites materials are strongly dependent on the residual aspect ratio, orientation, and distribution of the fibers, which are determined by the processing conditions. Present work is a systematic study of the influence of natural fiber concentration on its damage during all the steps involved in the composite compounding. The system under study is cellulose fiber-reinforced polypropylene. The fiber geometrical parameters - length, diameter, and aspect ratio - are measured, and their statistical distributions are assessed for different concentrations. It is found that the higher the fiber concentration, the lower the fiber damage. These results evidence a difference in behavior between the damage of flexible natural fiber and rigid ones. The results are analyzed in terms of fiber concentration regimes, fiber-fiber interaction, flexibility, and entanglements. Two competitive mechanisms of the fiber interaction are proposed for explaining the fiber damage behavior during the flow of the flexible natural fiber suspensions.